1991
DOI: 10.1523/jneurosci.11-09-02703.1991
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine, cocaine, and fencamfamine: relationship between locomotor and stereotypy response profiles and caudate and accumbens dopamine dynamics

Abstract: Using in vivo microdialysis, the caudate and nucleus accumbens dopamine (DA) responses to the psychomotor stimulants amphetamine (AMPH), cocaine (COC), and fencamfamine (FCF) were evaluated in rats concurrent with characterization of their behavioral response profiles. Doses of each stimulant that produced either enhanced locomotion or a prolonged period of intense focused stereotypies were examined to evaluate the quantitative relationships between stimulant-induced behaviors and changes in DA dynamics and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
143
2
6

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(175 citation statements)
references
References 35 publications
24
143
2
6
Order By: Relevance
“…Here it should be noted that, in our locomotion study (Figure 4,panel b), cocaine (20 mg/ kg) significantly enhanced locomotion in rats in acute withdrawal from the heroin. Thus, taken together, our results indicate that cocaine-induced DA activity in the Acb and cocaine-induced elevation of locomotor activity can be dissociated (Kuczenski et al, 1991). Interestingly, others have found that when the activity of the mesolimbic DA systems is tested in animals at later time points after withdrawal, repeated exposure to opioid drugs augments the DA response to electrically evoked release (Nestby et al, 1997) and to the administration of morphine (Spanagel et al, 1993).…”
Section: Effects Of Cocaine During Chronic Exposure To Heroin and Dursupporting
confidence: 52%
“…Here it should be noted that, in our locomotion study (Figure 4,panel b), cocaine (20 mg/ kg) significantly enhanced locomotion in rats in acute withdrawal from the heroin. Thus, taken together, our results indicate that cocaine-induced DA activity in the Acb and cocaine-induced elevation of locomotor activity can be dissociated (Kuczenski et al, 1991). Interestingly, others have found that when the activity of the mesolimbic DA systems is tested in animals at later time points after withdrawal, repeated exposure to opioid drugs augments the DA response to electrically evoked release (Nestby et al, 1997) and to the administration of morphine (Spanagel et al, 1993).…”
Section: Effects Of Cocaine During Chronic Exposure To Heroin and Dursupporting
confidence: 52%
“…Thus, perhaps a converse mechanism may be invoked to account for our data; pre-adolescent PPA administration may facilitate the development of cocaine-conditioned reward by reducing either the unconditioned or the conditioned aversive effects of cocaine. Although this mechanism is under intense investigation by our laboratory, our present observation that juvenile PPA treatment prevented the development of cocaine-induced locomotor sensitization, a classic animal model of psychosis (eg, Scheel-Kruger et al, 1977;Kuczenski et al, 1991;Post and Kopanda, 1976;Segal and Kuczenski, 1997), is consistent with this hypothesis.…”
Section: Juvenile Licit Drug Exposure and Stimulant Addiction-relatedsupporting
confidence: 78%
“…In addition to a sensitization of horizontal locomotion, the repeated administration of psychomotor stimulant drugs, such as cocaine, can induce a sensitization of intensely focused, stereotyped behaviors in rodents (including grooming, rearing, and sniffing) that can interfere with the expression of horizontal locomotion (eg, Kuczenski et al, 1991). Moreover, the expression of both stimulantinduced locomotion and stereotypy can become conditioned to the environment in which the drug is administered with repeated drug administration (Badiani et al, 2000;Badiani and Robinson, 2004;Browman et al, 1998;Pert et al, 1990;Robinson et al, 1998;Szumlinski et al, 1997).…”
Section: Cocaine-induced Stereotypymentioning
confidence: 99%
“…In all animals, ex vivo measurements gave higher specific striatal binding than in vivo measurements ( [7]. The 27% reduction in specific binding after administration of a dose of 2.5 mg/kg amphetamine seems rather minor compared to the massive dopamine release after amphetamine administration measured using microdialysis in previous studies [1,11]. The SPECT measurement is performed 2 h after amphetamine administration at that moment the effect of the amphetamine administration may already be reduced.…”
Section: Amphetamine-induced Dopamine Releasementioning
confidence: 70%